Studi Literatur tentang Kemampuan Guru dalam Memanajemen Pembelajaran Diferensiasi di Sekolah Dasar - Anisa Wijaya; Yufi Latmini Lasari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Education is a fundamental human need that plays a key role in shaping behavior and contributes to the development of a successful generation in Indonesia. However, during the learning process, teachers often encounter students who struggle to grasp the concepts being taught. This is due to the fact that each student brings unique characteristics and diverse backgrounds to the classroom. Teachers, therefore, must selec and develop various teaching materials that are suited to the individual needs of their students. The ability to tailor these materials effectively requires experience and knowledge in the development and selection of appropriate teaching tools for elementary schools. This study aims to assess the ability of elementary school teachers to manage differentiated learning, specifically through a literature review. The research will also identify how teachers approach the management of differentiated learning in the classroom and analyze the factors influencing their ability to implement this approach. By examining relevant literature, the study seeks to provide insight into the current capabilities of teachers and offer recommendations for improving the management of differentiated learning. The research employs a literature review method to gather data and draw conclusions about the best practices for managing differentiated learning in elementary school settings.